2012
DOI: 10.1182/blood-2011-09-378323
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab monotherapy in rituximab-refractory follicular lymphoma: results from a multicenter study

Abstract: New treatments are required for rituximabrefractory follicular lymphoma (FL). In the present study, patients with rituximabrefractory FL received 8 weekly infusions of ofatumumab (CD20 mAb; dose 1, 300 mg and doses 2-8, 500 or 1000 mg; N ‫؍‬ 116). The median age of these patients was 61 years, 47% had high-risk Follicular Lymphoma International Prognostic Index scores, 65% were chemotherapy-refractory, and the median number of prior therapies was 4. The overall response rate was 13% and 10% for the 500-mg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…[54][55][56] The nonlinear PK of these types of antibodies may in part be explained by binding of the antibodies to their respective targets, with a large component of target-mediated elimination after the first dose that is chemotherapy) have an elimination half-life in the magnitude of hours and rapidly achieve steady-state following administration (hours-days), while large molecules (e.g., mAbs) have a very long elimination half-life (in the magnitude of weeks) and may take up to 12 weeks to achieve steady-state. 65,66,69,70 …”
Section: -34mentioning
confidence: 99%
“…[54][55][56] The nonlinear PK of these types of antibodies may in part be explained by binding of the antibodies to their respective targets, with a large component of target-mediated elimination after the first dose that is chemotherapy) have an elimination half-life in the magnitude of hours and rapidly achieve steady-state following administration (hours-days), while large molecules (e.g., mAbs) have a very long elimination half-life (in the magnitude of weeks) and may take up to 12 weeks to achieve steady-state. 65,66,69,70 …”
Section: -34mentioning
confidence: 99%
“…20,21 Ofatumumab is being studied in patients with lymphomas either as a single agent or in combination with chemotherapy. 58,[72][73][74] Like rituximab, ofatumumab shows Type I anti-CD20 activity, including CD20 rafting and CDC activity, 35,75 but binding studies suggest that ofatumumab recognizes an epitope different from that of rituximab. While the binding of rituximab is prevented by mutation of the A170/P172 residues, site-directed mutagenesis has shown that such mutations in the large extracellular loop of CD20 do not affect the binding of ofatumumab.…”
mentioning
confidence: 99%
“…Recently, ofatumumab was shown to exert clinical responses in rituximab -refractory NHL patients patients 54 as well as in fludarabine / alemtuzumab -refratory CLL 55 . Similarly, some of the clinically tested anti-CD20 mAbs were engineered to enhance ADCC 56,57 but these modifications and their effects could not distinguish either CDC or ADCC as a crucial effector mechanism for the parental compound.…”
Section: Concluding ¨Per Analogiam¨ Is Not Possiblementioning
confidence: 99%